Water dispersible oil well cement elastic agent as well as preparation method and application thereof
Through the surface hydrophilicity and bonding ability of the modified rubber powder, the brittleness problem of cement stone under the impact force and the problem that rubber powder is difficult to disperse uniformly in cement slurry is solved, and the efficient toughening of cement stone and the improvement of cement strength are achieved.
Patent Information
- Application Number
- CN202311349537.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
AI Technical Summary
Existing cement stones are easily damaged under the action of impact force, resulting in failure of interlayer sealing performance, posing safety hazards, and rubber powder is difficult to disperse evenly in cement slurry, affecting rheology and thickening time.
Modifying the rubber powder, including the mixed reaction of acid solution, strong oxidant solution and silicate solution, improves the surface hydrophilicity and bonding ability of the rubber powder, and improves compatibility and cementitious ability.
The modified water-dispersed oil well cement elastogenic agent can be evenly dispersed in the cement slurry, significantly improving the elasticity and impact resistance of cement stone, enhancing its cement strength with cement, and ensuring long-term safe production of oil and gas wells and gas storage.
Smart Images

Figure BDA0004500031420000101 
Figure HDA0004500031680000011 
Figure HDA0004500031680000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of drilling engineering, and in particular relates to a water-dispersible oil well cement elastic agent, a preparation method and application thereof. Background Art
[0002] The quality of cementing stone is the premise for ensuring the long-term safe production of oil and gas wells. The exploitation of unconventional oil and gas reservoirs such as shale gas, coalbed methane and tight sandstone gas requires large-scale staged fracturing. Therefore, the cement sheath is required to have not only a certain strength, but also good impact resistance. During the operation of gas storage wells, they must withstand the temperature and alternating stress changes generated by injection and production at the same time. Conventional cement stone is easy to damage the mechanical integrity of the cement sheath due to its strong brittleness, resulting in the failure of the later interlayer sealing performance, which will cause potential safety hazards to the later production increase measures of oil and gas wells and the smooth operation of gas storage. Therefore, it is necessary to improve the toughness and impact resistance of cement stone.
[0003] At present, elastic materials are usually added to cement paste to optimize the mechanical properties of cement paste. Commonly used elastic materials include waste rubber powder, synthetic latex, modified resin, etc.
[0004] Among them, rubber powder is a product obtained by crushing and processing waste rubber products such as waste tires and waste hoses. The molecules present a three-dimensional spatial network structure, have elasticity similar to natural rubber, and are not sticky and plastic. They can quickly deform greatly under the action of external forces, and can return to their original state when the external force is removed. They can also adapt to a wide range of temperature. When it is used as an elastic agent for oil well cement, when the cement stone is subjected to impact force, it can absorb vibration energy, thereby improving the impact resistance of the cement ring. It not only provides high-quality and low-cost cement toughening agent products for cementing operations, but also helps to solve the increasingly serious environmental pollution problem of waste rubber, with good economic and social benefits.
[0005] However, since the surface of unmodified rubber powder is inert, poorly hydrophilic, and poorly compatible with cement paste, it is difficult to disperse evenly when added to the cement slurry system, and it is easy to aggregate into agglomerates, affecting the rheology and thickening time of the cement slurry. In addition, rubber particles are tough materials and cement paste is brittle materials, and the bonding ability between the two is poor. Therefore, the surface of waste rubber powder must be modified before use as an elastic agent for oil well cement. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a water-dispersible oil well cement elastic agent with good hydrophilicity and strong cement bonding ability, and a preparation method and application thereof.
[0007] The invention provides a water-dispersible oil well cement elastic agent, which is obtained by modifying rubber powder with a modifier; the modifier comprises an acid solution, a strong oxidant solution and a silicate solution.
[0008] Preferably, the particle size of the rubber powder is 0.18-0.45 mm.
[0009] Preferably, the mass ratio of the rubber powder to the acid solution is (60-80):(5-10);
[0010] The mass concentration of the acid solution is 10% to 20%.
[0011] Preferably, the mass ratio of the rubber powder to the strong oxidant solution is (60-80): (2-6);
[0012] The mass concentration of the strong oxidant solution is 1% to 15%.
[0013] Preferably, the mass ratio of the rubber powder to the silicate solution is (60-80):(5-10);
[0014] The mass concentration of the silicate solution is 5% to 20%.
[0015] Preferably, the acid solution is selected from one or more of formic acid solution, acetic acid solution, hydrochloric acid solution and sulfuric acid solution;
[0016] The strong oxidant in the strong oxidant solution is selected from one or more of sodium perborate, hydrogen peroxide, peracetic acid, sodium dichromate, potassium permanganate and sodium percarbonate;
[0017] The silicate in the silicate solution is selected from sodium silicate and / or potassium silicate.
[0018] The present invention also provides a method for preparing a water-dispersible oil well cement elastic agent, comprising the following steps:
[0019] S1) mixing the rubber powder, the acid solution and the strong oxidant solution for reaction, adding a pH adjuster to obtain an intermediate product;
[0020] S2) stirring and reacting the intermediate product with a silicate solution to obtain a water-dispersible oil well cement elastic agent.
[0021] Preferably, the temperature of the mixed reaction in step S1) is 30°C to 50°C; the time of the mixed reaction is 1 to 3 hours; the amount of the pH regulator is such that the pH value of the reaction system is 7 to 9;
[0022] The stirring reaction time in step S2) is 1 to 2 hours.
[0023] Preferably, the pH adjuster is an alkali metal hydroxide solution; the mass concentration of the alkali metal hydroxide solution is 5% to 15%; the mass ratio of the rubber powder to the pH adjuster is (60 to 80): (1 to 5).
[0024] The present invention also provides a cement slurry, comprising the water-dispersible oil well cement elastic agent.
[0025] The present invention provides a water-dispersible oil well cement elastic agent, which is obtained by modifying rubber powder with a modifier; the modifier includes an acid solution, a strong oxidant solution and a silicate solution. Compared with the prior art, the water-dispersible oil well cement elastic agent provided by the present invention maintains the original internal structural characteristics of rubber, namely, elastic toughness and temperature resistance, and only changes the surface hydrophilicity and surface bonding ability through surface solid phase chemical reaction, thereby improving its compatibility with inorganic materials and improving the bonding ability of rubber particles and cement. In addition, the raw materials of the water-dispersible oil well cement elastic agent are abundant and widely available, the preparation process is safe, simple and easy, and does not involve complex production equipment and devices. The reagents used are cheap and easy to obtain, and there is no wastewater and waste residue discharge. It is safe and environmentally friendly, and it is easy to realize large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a state diagram of a reaction system with a solid content of 70% during the rubber powder modification process in Example 1 of the present invention;
[0027] Figure 2 This is the floating state diagram of rubber powder in cement stone before modification;
[0028] Figure 3 This is a diagram showing the floating state of the oil well cement elastic agent in the cement stone in Example 2 of the present invention;
[0029] Figure 4 This is a diagram showing the water dispersibility testing process of the rubber powder raw material of the present invention and the modified rubber powder obtained in Examples 1 to 6;
[0030] Figure 5 This is the infrared spectrum of the oil well cement elastic agent obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] The invention provides a water-dispersible oil well cement elastic agent, which is obtained by modifying rubber powder with a modifier; the modifier comprises an acid solution, a strong oxidant solution and a silicate solution.
[0033] According to the present invention, the particle size of the rubber powder is preferably 0.18-0.45 mm, more preferably 0.2-0.4 mm, and even more preferably 0.21-0.35 mm; the rubber powder can be any rubber powder well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably one or more of waste tire rubber powder, waste rubber sheet rubber powder, waste moisture-proof mat rubber powder, waste hose rubber powder and waste rubber shoe rubber powder; the main component of the rubber powder is preferably one or more of natural rubber, butadiene rubber, styrene-butadiene rubber, nitrile rubber, ethylene-propylene rubber and chloroprene rubber.
[0034] The modifier used for modifying rubber powder in the present invention comprises an acid solution, a strong oxidant solution and a silicate solution.
[0035] Wherein, the acid solution is preferably a small molecule organic acid solution and / or an inorganic acid solution, more preferably one or more of an acid solution, a strong oxidant solution and a silicate solution; the mass concentration of the acid solution is preferably 5% to 15%, more preferably 8% to 15%, and even more preferably 10% to 15%; in some embodiments provided by the present invention, the mass concentration of the acid solution is specifically 10%, 15% or 13%; the mass ratio of the rubber powder to the silicate solution is preferably (60 to 80): (5 to 10); in some embodiments provided by the present invention, the mass ratio of the rubber powder to the silicate solution is specifically 60:5, 65:10, 70:5, 65:7, 75:6 or 80:8.
[0036] The strong oxidant in the strong oxidizing solution is preferably one or more of sodium perborate, hydrogen peroxide, peracetic acid, sodium dichromate, potassium permanganate and sodium percarbonate; the mass concentration of the strong oxidizing solution is preferably 1% to 20%, more preferably 1.5% to 20%; in the embodiments provided by the present invention, the mass concentration of the strong oxidizing solution is specifically 1.5%, 15%, 5%, 10% or 20%; the mass ratio of the rubber powder to the strong oxidizing solution is preferably (60 to 80): (2 to 6); in some embodiments provided by the present invention, the mass ratio of the rubber powder to the strong oxidizing solution is specifically 60:3, 65:2, 70:5, 65:4, 75:6 or 80:2.
[0037] The silicate in the silicate solution is preferably sodium silicate and / or potassium silicate; the modulus of the silicate in the silicate solution is preferably 2-3, more preferably 2-2.5, and more preferably 2.2; the mass concentration of the silicate solution is preferably 5%-20%, more preferably 8%-20%, and more preferably 8%-; in some embodiments provided by the present invention, the mass concentration of the silicate solution is specifically 10%, 12%, 15% or 8%; the mass concentration of the rubber powder and the silicate solution is preferably (60-80):(5-10); in some embodiments provided by the present invention, the mass concentration of the rubber powder and the silicate solution is specifically 60:5, 65:7, 70:6, 65:10, 75:8 or 80:7.5.
[0038] Since the modification of the silicate solution needs to be carried out in a neutral or weakly alkaline environment, it is preferred to further include a pH regulator; the pH regulator is preferably an alkali metal hydroxide solution, more preferably a sodium hydroxide solution and / or a potassium hydroxide solution; the mass concentration of the alkali metal hydroxide solution is preferably 5% to 15%, more preferably 7% to 12%, and more preferably 7% to 10%; the mass ratio of the rubber powder to the pH regulator is preferably (60 to 80): (1 to 5), more preferably (60 to 80): (2 to 5), and more preferably (60 to 80): (2 to 4); in some embodiments provided by the present invention, the mass ratio of the rubber powder to the pH regulator is specifically 60:2, 65:2.5, 70:3, 65:3, 75:4 or 80:3.
[0039] In the present invention, unless otherwise specified, the solution refers to an aqueous solution.
[0040] The water-dispersible oil well cement elastic agent provided by the present invention maintains the original internal structural characteristics of rubber, namely, elastic toughness and temperature resistance, and only changes the surface hydrophilicity and surface bonding ability through surface solid-phase chemical reaction, thereby improving its compatibility with inorganic materials and improving the bonding ability between rubber particles and cement. In addition, the raw materials of the water-dispersible oil well cement elastic agent are abundant and widely available, the preparation process is safe, simple and easy, and no complicated production equipment and devices are involved. The reagents used are cheap and easy to obtain, no wastewater and waste residue are discharged, and it is safe and environmentally friendly, and large-scale industrial production can be easily realized.
[0041] The present invention also provides a method for preparing the above-mentioned water-dispersible oil well cement elastic agent, comprising the following steps: S1) mixing and reacting rubber powder, an acid solution and a strong oxidant solution, adding a pH value regulator to obtain an intermediate product; S2) stirring and reacting the intermediate product with a silicate solution to obtain a water-dispersible oil well cement elastic agent.
[0042] The present invention has no special restrictions on the sources of all raw materials, and any raw materials available on the market can be used; the types and proportions of the rubber powder, acid solution, strong oxidant solution, pH adjuster and silicate solution are the same as those described above and will not be repeated here.
[0043] The rubber powder, the acid solution and the strong oxidant solution are mixed and reacted; in the present invention, the acid solution and the strong oxidant solution are preferably slowly added to the rubber powder in sequence; the mixing reaction is preferably carried out under stirring; the temperature of the mixing reaction is preferably 30°C to 50°C; the mixing reaction time is preferably 1 to 3 hours, more preferably 1 to 2 hours.
[0044] After the mixed reaction, a pH adjuster is added to obtain an intermediate product; the amount of the pH adjuster is preferably such that the pH value of the reaction system is 7 to 9.
[0045] The intermediate product is reacted with a silicate solution under stirring, preferably the silicate solution is reacted under stirring; the temperature of the stirring reaction is preferably 30°C to 50°C; the time of the stirring reaction is preferably 1 to 2 hours; in some embodiments provided by the present invention, the time of the stirring reaction is specifically 1 hour, 1.5 hours or 2 hours.
[0046] After stirring and reacting, the mixture is preferably dried and crushed to obtain a water-dispersible oil well cement elastic agent; the drying temperature is preferably 50°C to 80°C, more preferably 60°C to 80°C; the particle size of the water-dispersible oil well cement elastic agent is preferably 0.18 to 0.45 mm.
[0047] The invention uses rubber powder as the main raw material, and sequentially adds a brazing acid solution, a strong oxidant solution and a silicate solution to carry out surface solid-phase chemical reaction, so that the surface of the rubber powder has hydrophilic groups and -OH, Si-O and other groups, thereby obtaining modified rubber powder with good surface hydrophilicity and high cement bonding strength. The modified rubber powder can be evenly dispersed in cement slurry and used as an elastic agent for oil well cement, and can significantly improve the brittleness of cement stone, improve its elastic toughness and impact resistance, and enhance the cement stone bonding strength.
[0048] The present invention also provides a cement slurry, comprising the water-dispersible oil well cement elastic agent.
[0049] According to the present invention, the mass of the water-dispersible oil well cement elastic agent is preferably 1% to 10% of the mass of the cement slurry, more preferably 2% to 8%, further preferably 2% to 5%, and most preferably 3% to 4%.
[0050] According to the present invention, the cement slurry preferably also includes cement; the cement can be cement well known to those skilled in the art without any special limitation, and the embodiments provided in the present invention are specifically described by taking Grade G cement as an example; the mass of the cement is preferably 40% to 80% of the mass of the cement slurry, more preferably 50% to 70%, further preferably 60% to 70%, and most preferably 65% to 67%.
[0051] The water-dispersible oil well cement elastic agent provided by the present invention can improve the brittleness of cement paste, increase the elastic toughness and impact resistance, and enhance the bonding ability with the cement paste interface.
[0052] In order to further illustrate the present invention, the present invention provides a water-dispersible oil well cement elastic agent, a preparation method and application thereof are described in detail below in conjunction with embodiments.
[0053] The reagents used in the following examples are all commercially available, and the rubber powder used is from Lingshou County Xinlong Mineral Products Processing Plant; the modulus of sodium silicate in the sodium silicate aqueous solution used in the examples is 2.2.
[0054] Comparative Example 1
[0055] Weigh 60 parts of rubber powder (waste tire rubber powder, particle size 0.30mm), slowly add 5 parts of 10% formic acid solution and 3 parts of 1.5% sodium perborate solution in sequence under mixing state, mix evenly, heat to 40°C and mix for 2h, add 2 parts of 7% sodium hydroxide solution under mixing state, keep mixing at the above temperature for 2h to obtain the reaction product; dry and crush the product at 65°C to obtain an oil well cement elastic agent with a particle size of 0.30mm.
[0056] Example 1
[0057] Weigh 60 parts of rubber powder (waste tire rubber powder, particle size 0.30mm), slowly add 5 parts of 10% formic acid solution and 3 parts of 1.5% sodium perborate solution in sequence under mixing state, mix evenly, heat to 40°C and mix for 2h, add 2 parts of 7% sodium hydroxide solution under mixing state; then slowly add 5 parts of 10% sodium silicate solution under mixing state, keep the above temperature and mix for 2h to obtain the reaction product; dry and crush the product at 65°C to obtain an oil well cement elastic agent with a particle size of 0.30mm.
[0058] Figure 1 This is a state diagram of a reaction system with a solid content of 70% during the rubber powder modification process in Example 1.
[0059] Example 2
[0060] Weigh 65 parts of rubber powder (waste tire rubber powder, particle size 0.25mm), slowly add 10 parts of 10% formic acid solution and 2 parts of 15% hydrogen peroxide solution in sequence under mixing state, mix evenly, heat to 40°C and mix for 2.0h, add 2.5 parts of 7% potassium hydroxide solution under mixing state; then slowly add 7 parts of 12% sodium silicate solution under mixing state, keep the above temperature and mix for 1.0h to obtain the reaction product; dry and crush the product at 60°C to obtain an oil well cement elastic agent with a particle size of 0.25mm.
[0061] Example 3
[0062] Weigh 70 parts of rubber powder (waste tire rubber powder, particle size 0.21mm), slowly add 5 parts of 15% hydrochloric acid solution and 5 parts of 5% peracetic acid solution in sequence under mixing state, mix evenly, heat to 35°C and mix for 1.5h, add 3 parts of 10% sodium hydroxide solution under mixing state; then slowly add 6 parts of 15% potassium silicate solution under mixing state, keep the above temperature and mix for 2.0h to obtain the reaction product; dry and crush the product at 65°C to obtain an oil well cement elastic agent with a particle size of 0.21mm.
[0063] Example 4
[0064] Weigh 65 parts of rubber powder (waste hose rubber powder, particle size 0.35mm), slowly add 7 parts of 13% hydrochloric acid solution and 4 parts of 10% hydrogen peroxide solution in sequence under mixing state, mix evenly, heat to 30°C and mix for 1.0h, add 3 parts of 10% potassium hydroxide solution under mixing state; then slowly add 10 parts of 8% sodium silicate solution under mixing state, keep mixing at the above temperature for 1.0h to obtain the reaction product; dry and crush the product at 75°C to obtain an oil well cement elastic agent with a particle size of 0.35mm.
[0065] Example 5
[0066] Weigh 75 parts of rubber powder (waste tire rubber powder, particle size 0.25mm), slowly add 6 parts of 10% sulfuric acid solution and 6 parts of 5% potassium permanganate solution in sequence under mixing state, mix evenly, heat to 50°C and mix for 2.5h, add 4 parts of 8% potassium hydroxide solution under mixing state; then slowly add 8 parts of 10% potassium silicate solution under mixing state, keep the above temperature and mix for 1.0h to obtain the reaction product; dry and crush the product at 70°C to obtain an oil well cement elastic agent with a particle size of 0.25mm.
[0067] Example 6
[0068] Weigh 80 parts of rubber powder (waste tire rubber powder, particle size 0.25mm), slowly add 8 parts of 15% hydrochloric acid solution and 2 parts of 20% hydrogen peroxide solution in sequence under mixing state, mix evenly, heat to 40°C and mix for 1.5h, add 3 parts of 10% sodium hydroxide solution under mixing state; then slowly add 7.5 parts of 10% sodium silicate solution under mixing state, keep mixing at the above temperature for 1.5h to obtain a reaction product; dry and crush the product at 80°C to obtain an oil well cement elastic agent with a particle size of 0.25mm.
[0069] Comparative Example 2
[0070] For comparison, 800 parts of cement (Jiahua G grade) and 352 parts of water were used to prepare cement slurry according to GB19139. After curing at 80℃ / 21MPa for 48h, the elastic modulus of the cement stone was measured to be 9.74GPa, the compressive strength was 38.26MPa, and the bonding strength was 3.52MPa.
[0071] Comparative Example 3
[0072] For comparison, 800 parts of cement (Jiahua G grade), 40 parts of unmodified rubber powder (waste tire rubber powder, particle size 0.30mm), and 352 parts of water were used to prepare cement slurry according to GB19139. After curing at 80℃ / 21MPa for 48h, the elastic modulus of the cement stone was measured to be 6.78GPa, the compressive strength was 34.65MPa, and the bonding strength was 3.87MPa.
[0073] Comparative Example 4
[0074] For comparison, 800 parts of cement (Jiahua G grade), 40 parts of the oil well cement elastic agent described in Comparative Example 1, and 352 parts of water were used to prepare cement slurry according to GB19139. After curing at 80°C / 21MPa for 48h, the elastic modulus of the cement stone was measured to be 6.15GPa, the compressive strength was 37.45MPa, and the bonding strength was 3.91MPa.
[0075] Example 7
[0076] 800 parts of cement (Jiahua G grade), 40 parts of the oil well cement elastic agent described in Example 1, and 352 parts of water were used to prepare cement slurry according to GB19139. After curing at 80°C / 21MPa for 48 hours, the elastic modulus of the cement paste was measured to be 5.69GPa, the compressive strength was 35.72MPa, and the bonding strength was 4.21MPa.
[0077] Example 8
[0078] 800 parts of cement (Jiahua G grade), 40 parts of the oil well cement elastic agent described in Example 3, and 352 parts of water were used to prepare cement slurry according to GB19139. After curing at 80°C / 21MPa for 48 hours, the elastic modulus of the cement paste was measured to be 5.88GPa, the compressive strength was 37.05MPa, and the bonding strength was 4.39MPa.
[0079] Example 9
[0080] 800 parts of cement (Jiahua G grade), 40 parts of the oil well cement elastic agent described in Example 5, and 352 parts of water were used to prepare cement slurry according to GB19139. After curing at 80°C / 21MPa for 48 hours, the elastic modulus of the cement paste was measured to be 5.96GPa, the compressive strength was 38.32MPa, and the bonding strength was 4.25MPa.
[0081] Figure 2 It is the floating state of rubber powder in cement stone before modification. Figure 3 The floating state of the modified rubber powder in Example 2 in the cement paste. Figure 2 and Figure 3 By comparison, it can be seen that the modified rubber powder does not accumulate on the top of the cement slurry cup, but is dispersed into the cement slurry.
[0082] It can be seen from Examples 7 to 9 that, compared with Comparative Examples 1 and 2, the mechanical properties of the cement paste to which the modified rubber powder is added are significantly improved, the elastic modulus is significantly reduced, and the bonding strength is significantly improved.
[0083] The water dispersibility of the rubber powder raw material and the elastic agent in Examples 1 to 6 was evaluated, and the results are shown in Table 1. The test process is as follows: Figure 4 .
[0084] The detection method is as follows:
[0085] Measure 200 mL of distilled water into a beaker, start an electric stirrer at 800 r / min, add 4.0 g (accurate to 0.01 g) of the sample kept at a constant temperature of 105°C ± 3°C for 2 h into the stirred water, and continue stirring for 15 min, stopping at least twice during the stirring to scrape off the sample adhering to the container.
[0086] Transfer the solution in the beaker to the vacuum valve funnel, and rinse the inner wall of the beaker with 50 mL of distilled water 2-3 times to transfer all the samples into the vacuum valve funnel. Fix the vacuum valve funnel and let it stand for 15 minutes, and release 90% of the suspension into the beaker.
[0087] Drain the remaining suspension in the vacuum valve funnel into a constant-weight rapid qualitative filter paper, and rinse the sample adhering to the inner wall of the vacuum valve funnel with distilled water until the sample is completely transferred to the filter paper, filter, transfer the filter paper with the precipitate to a beaker, keep it at a constant temperature of 105℃±3℃ for 4 hours, take it out and put it in a desiccator, cool it to room temperature, and weigh the mass of the filter paper and the precipitate (accurate to 0.01g). Dispersibility is calculated by the following formula.
[0088]
[0089] In the formula: Z - dispersibility, %; m0 - the mass of the sample, in grams (g); m1 - the mass of the filter paper, in grams (g); m2 - the mass of the filter paper and sediment after drying, in grams (g).
[0090] Table 1 Evaluation of water dispersibility
[0091] Example Water dispersibility, % Unmodified rubber powder 0.0 Comparative Example 1 75.0 Example 1 98.2 Example 2 97.6 Example 3 97.4 Example 4 99.1 Example 5 96.9 Example 6 98.7
[0092] It can be seen from Table 1 that, compared with the unmodified rubber powder, the surface hydrophilicity of the modified rubber powder is significantly improved, and the water dispersibility reaches more than 95%.
[0093] The oil well cement elastic agent obtained in Example 2 was analyzed by infrared spectroscopy, and its infrared spectrum was obtained as shown in FIG. Figure 5 As shown. Figure 5 It can be seen that the surface has hydrophilic groups as well as -OH, Si-O and other groups.
[0094] In summary, the modified rubber powder has good hydrophilicity and high bonding ability with cement paste while maintaining the original elasticity and toughness, which improves the elasticity and toughness, impact resistance and bonding strength of cement paste. In addition, the three modifiers, acid solution, strong oxidant solution and silicate solution, cannot achieve the desired hydrophilicity and improve the bonding strength with cement paste by using only one modifier.
[0095] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention, but the present invention is not limited thereto. Those skilled in the art can understand that within the technical concept of the present invention, the technical solution of the present invention can be modified, or some technical features can be combined in any other way. These modifications or combinations do not make the essence of the corresponding technical solution deviate from the spirit and scope of each implementation of the technical solution of the present invention, and should be regarded as the contents disclosed by the present invention, which belong to the protection scope of the present invention.
Claims
1. A water-dispersible oil well cement elastic agent, characterized in that: The rubber powder is obtained by modifying the rubber powder with a modifier; the modifier includes an acid solution, a strong oxidant solution and a silicate solution.
2. The water-dispersible oil well cement elastic agent according to claim 1, characterized in that: The particle size of the rubber powder is 0.18-0.45 mm.
3. The water-dispersible oil well cement elastic agent according to claim 1, characterized in that: The mass ratio of the rubber powder to the acid solution is (60-80):(5-10); The mass concentration of the acid solution is 10% to 20%.
4. The water-dispersible oil well cement elastic agent according to claim 1, characterized in that: The mass ratio of the rubber powder to the strong oxidant solution is (60-80): (2-6); The mass concentration of the strong oxidant solution is 1% to 15%.
5. The water-dispersible oil well cement elastic agent according to claim 1, characterized in that: The mass ratio of the rubber powder to the silicate solution is (60-80):(5-10); The mass concentration of the silicate solution is 5% to 20%.
6. The water-dispersible oil well cement elastic agent according to claim 1, characterized in that: The acid solution is selected from one or more of formic acid solution, acetic acid solution, hydrochloric acid solution and sulfuric acid solution; The strong oxidant in the strong oxidant solution is selected from one or more of sodium perborate, hydrogen peroxide, peracetic acid, sodium dichromate, potassium permanganate and sodium percarbonate; The silicate in the silicate solution is selected from sodium silicate and / or potassium silicate.
7. A method for preparing a water-dispersible oil well cement elastic agent, characterized in that: The following steps are involved: S1) mixing the rubber powder, the acid solution and the strong oxidant solution for reaction, adding a pH adjuster to obtain an intermediate product; S2) stirring and reacting the intermediate product with a silicate solution to obtain a water-dispersible oil well cement elastic agent.
8. The preparation method according to claim 7, characterized in that: The temperature of the mixed reaction in step S1) is 30°C to 50°C; the time of the mixed reaction is 1 to 3 hours; the amount of the pH regulator is such that the pH value of the reaction system is 7 to 9; The stirring reaction time in step S2) is 1 to 2 hours.
9. The preparation method according to claim 7, characterized in that: The pH value regulator is an alkali metal hydroxide solution; the mass concentration of the alkali metal hydroxide solution is 5% to 15%; the mass ratio of the rubber powder to the pH value regulator is (60 to 80): (1 to 5).
10. A cement slurry, characterized in that: The invention comprises the water-dispersible oil well cement elastic agent according to any one of claims 1 to 6 or the water-dispersible oil well cement elastic agent prepared by any one of the preparation methods according to claims 7 to 9.